Influence of the HLA-DRB1 locus on susceptibility and severity in rheumatoid arthritis. - Hall, F; Weeks, D; Camilleri, J; Williams, L; Amos, N; Darke, C; Gibson, K; Pile, K; Wordsworth, B; Jessop, J (1996)
We examined HLA-DR genotype risk in 288 patients with rheumatoid arthritis who were carefully categorized for disease severity. Five hundred ethnically-matched bone-marrow donors were controls. A hierarchy of positive allelic associations was noted with DRB1*0401 (p < 10(-38), *0404,8 (p < 10(-43), *0405 (p < 10(-8), *10 (p < 10(-3) and *0101,2 (p < 10(-2), while DRB1*0403 was negatively associated (p = 0.02). The DRB1 genotype relative risks (and 95% CIs) for RA were: *0404,5,8/*0404,5,8 = 36.2 (15-87), *0401/*0404,5,8 = 31.3 (18-55), *401/*0401 = 18.8 (11-35), *0101,2/*0404,5,8 = 6.0 (2-14), *0101,2/*0401 = 6.4 (3-12), *0101,2/*0101,2 = 1.3 (0.3-6), *10/*0404,5,8 = 27.8 (5-148), *10/*0401 = 20.8 (5-89), *10/*0101,2 = 22.3 (5-96), *0404,5,8/DRX = 5.0 (3-8), *0401/DRX = 4.7 (3-7), *0101,2/DRX = 2.3 (1.4-4), *10/DRX = 3.4 (0.8-14). No significant correlation of DRB1 genotypes was found with severity of RA as judged by nodules or articular erosions.